Consumer participation and pro-poor regulation in Latin America - Cecilia Ugaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
In spite of not being `public goods' in the strict sense of the term, public provision has been a common way of supplying utilities services around the world. Among the major reasons underlying the dominant position of the public sector as the provider of infrastructure are the recognition of the economic and political importance of infrastructure for development, and the faith that government provision could offset market failures characterizing the utilities market. However, under public provision, universal access to the services remained elusive, with large sectors of the population being excluded. At the same time, the financing of services became a heavy burden on government budgets. As documented elsewhere in the research project, a major move towards privatization started in Latin America in the 1980s and early 1990s following the pioneering experiences of Chile's and the UK's infrastructure reform. – utilities ; privatization ; public goods ; regulation
Keywords: L4; L5; L9; H4; D1; 330; Versorgungswirtschaft; Privatisierung; Regulierung; Lateinamerika